1979
DOI: 10.1111/j.1095-8649.1979.tb03516.x
|View full text |Cite
|
Sign up to set email alerts
|

The immunoglobulin of the brown trout, Salmo trutta and its concentration in the serum of antigen‐stimulated and non‐stimulated fish

Abstract: Immunoglobulin production in the primary and secondary immune response of brown trout to keyhole limpet haemocyanin has been investigated including the effect of dose size, route and number of injections, and the use of adjuvant. Antibody activity was found in the first fraction from Sephadex G200 and in the second from Sepharose 6B. Trout immunoglobulin had pa-yl electrophoretic mobility, and S,,, of 16.7 and an approximate molecular weight of 670 000 daltons. It was sensitive to dithiothreitol and stable at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

1983
1983
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 34 publications
4
18
0
1
Order By: Relevance
“…The activity was lost after treatment with 2-ME, a substance used to reduce the disulfide bounds of immunoglobulins. This result agrees with reports on other fish where the activity of the immunoglobulins was completely abolished by 2-ME treatment (Evelyn 1971, Clem & McLean 1975, Ingram & Alexander 1979. Studies on the separation and purification of other bony fish serum antibodies demonstrated that only the IgM class occurs (Ambrosius et al 1982).…”
Section: Discussionsupporting
confidence: 89%
“…The activity was lost after treatment with 2-ME, a substance used to reduce the disulfide bounds of immunoglobulins. This result agrees with reports on other fish where the activity of the immunoglobulins was completely abolished by 2-ME treatment (Evelyn 1971, Clem & McLean 1975, Ingram & Alexander 1979. Studies on the separation and purification of other bony fish serum antibodies demonstrated that only the IgM class occurs (Ambrosius et al 1982).…”
Section: Discussionsupporting
confidence: 89%
“…This is the first report of plasma IgM levels in Pacific herring. Serum IgM concentrations have been reported for several other species: Oncorhynchus mykiss, 0.6 to 9.3 mg rnl-' ) and 3.3 mg ml-' (Olesen & Jsrgensen 1986); Salmo trutta, 7.3 mg ml-' (Ingram & Alexander 1979); Oncorhynchus keta, 0.63 to 0.72 mg rnl-' (Kobayashi et al 1982); and Scophthalmus maximus, 3.35 to 11.14 mg ml-' (Estevez et al 1995). The IgM component of total serum protein in fish has been reported as 6.4 % (Mochida et al 1994), 10 % (Ingram & Alexander 1979), and 7.5 to hoferi infection, a variety of nonspecific histologic 18% (Estevez et al 1995).…”
Section: Elisa Parametersmentioning
confidence: 99%
“…1 (KusuDA et al, 1981). Furthermore, in immunized brown trout the immunoglobulin concentration increased and ranged from 7.5 to 12.9 % after one injection, and from 12.6 to 16.8% after two or three injections (INGRAM et al, 1979).…”
Section: Resultsmentioning
confidence: 99%